Exploring the Gap between Museum Policy and Practice: a Comparative analysis of Scottish, English and Welsh Local Authority Museum Services - McCall, Vikki (Museum and Society, 2017)
This paper explores the gap between museum policy and practice in the United Kingdom (UK) by offering empirical evidence from a comparative street-level analysis of museum services in Scotland, England and Wales. Exploring devolution in cultural services from the ground-level using Lipsky’s (1980) ‘streetlevel’ approach gives new insights to the role of ground-level workers in cultural policy. It shows that museum workers had an awareness of national policies, but implementation was mainly influenced by a mixture of challenges in the everyday delivery of the museum services studied. Museum workers understood policy as something symbolic rather than relating to action, which reinforced policy distance. Workers at the ground-level had more similarities than differences throughout Scotland, England and Wales and the structural challenges within museum services indicated a complex negotiation that increased agency at the ground-level. These findings outline the potential limitations of written national and international policy in the cultural sector as it is the activities, values and behaviours at the front-line of cultural services that ultimately creates policy in the cultural sector. 1 Key words: Cultural policy; museum workers; UK devolution; policy distance; street-level analysis; Lipsky